Revisiting the fate of buds: size and position drive bud mortality and bursting in two coexisting Mediterranean Quercus species with contrasting leaf habit - Alla, Arben Q.; Julio Camarero, J.; Palacio, Sara; Montserrat-Martí, Gabriel (TREES-STRUCTURE AND FUNCTION, 2013)
Understanding the relationships between bud size and position and bud fate through time is crucial for identifying and subsequently modeling the mechanisms underlying tree architecture. However, there is a lack of information on how bud size drives crown architectural patterns in coexisting tree species. We studied bud demography in two coexisting Mediterranean oak species with contrasting leaf habit (Quercus ilex, evergreen; Q. faginea, deciduous). The main objective was to analyse the effect of bud size on the fate of buds with different positions along the shoot (apical, leaf axillary and scale-cataphyll axillary buds). The number, length and position of all buds and stems were recorded in marked branches during 4 years. Study species presented different strategies in bud production and lifespan. The evergreen species showed greater mortality rate than the deciduous one, which produced larger buds. Bud size and position were highly related since apical buds where longer than axillary ones and bud length declined basipetally along the stem. Apical buds had also higher chances of bursting than axillary ones. Within positions, longer buds presented a higher probability of bursting than shorter ones, although no absolute size threshold was found below which bud bursting was impaired. In Q. ilex, four-year-old buds were still viable and able to burst, whereas in Q. faginea practically all buds burst in their first year or died soon after. Such different bud longevities may indicate contrasting strategies in primary growth between both species. Q. ilex is able to accumulate viable buds for several ages, whereas Q. faginea seems to rely on the production of large current-year buds with high bursting probability under favourable environmental conditions.
The following values have no corresponding Zotero field: pub-location: 233 SPRING ST, NEW YORK, NY 10013 USA publisher: SPRINGER
Keywords: Bud demography; Bud position; Bud size; Budburst; Quercus faginea; Quercus ilex subsp ballota

Seasonal and inter-annual variability of bud development as related to climate in two coexisting Mediterranean Quercus species - Alla, Arben Q.; Camarero, J. Julio; Montserrat-Martí, Gabriel (Annals of Botany, 2013)
Background and Aims In trees, bud development is driven by endogenous and exogenous factors such as species and climate, respectively. However, knowledge is scarce on how these factors drive changes in bud size across different time scales.Methods The seasonal patterns of apical bud enlargement are related to primary and secondary growth in two coexisting Mediterranean oaks with contrasting leaf habit (Quercus ilex, evergreen; Quercus faginea, deciduous) over three years. In addition, the climatic factors driving changes in bud size of the two oak species were determined by correlating bud mass with climatic variables at different time scales (from 5 to 30 d) over a 15-year period.Key Results The maximum enlargement rate of buds was reached between late July and mid-August in both species. Moreover, apical bud size increased with minimum air temperatures during the period of maximum bud enlargement rates.Conclusions The forecasted rising minimum air temperatures predicted by climatic models may affect bud size and consequently alter crown architecture differentially in sympatric Mediterranean oaks. However, the involvement of several drivers controlling the final size of buds makes it difficult to predict the changes in bud size as related to ongoing climate warming.
10.1093/aob/mcs24710.1093/aob/mcs247
Keywords: Bud size; current-year stem; Quercus faginea; quercus ilex subsp. ballota; summer growth; Temperature

Acorn production is linked to secondary growth but not to declining carbohydrate concentrations in current-year shoots of two oak species - Alla, Arben Q.; Camarero, J. Julio; Maestro-Martínez, Melchor; Montserrat-Martí, Gabriel (Trees, 2011)
In trees, reproduction constitutes an important resource investment which may compete with growth for resources. However, detailed analyses on how growth and fruit production interact at the shoot level are scarce. Primary canopy growth depends on the development of current-year shoots and their secondary growth might also inﬂuence the number and size of fruits supported by them. We hypothesise that an enhanced thickening of currentyear shoots is linked positively to acorn production in oaks. We analysed the effect of acorn production on shoot growth of two co-occurring Mediterranean oak species with contrasting leaf habit (Quercus ilex, Quercus faginea). Length and cross-sectional area of current-year shoots, apical bud mass, number of leaves and acorns, xylem and conductive area, number of vessels of acorn-bearing and non-bearing shoots were measured in summer and autumn. Nitrogen and carbohydrates analyses were also performed in stems and leaves of both shoot types. Stem cross-sectional area increased in acorn-bearing shoots when compared with non-bearing shoots for both species and such surplus secondary growth was observed since summer. In bearing shoots, the total transversal area occupied by vessels decreased signiﬁcantly from basal to apical positions along the stem as did the xylem area and the number of vessels. Leaves of bearing shoots showed lower nitrogen concentration than those of non-bearing shoots. Carbohydrate concentrations did not differ in stems and leaves as a function of the presence of acorns. Such results suggest that carbohydrates may preferentially be allocated towards reproductive shoots, possibly through enhanced secondary growth, satisfying all their carbon demands for growth and reproduction. Our ﬁndings indicate that acorn production in the two studied oaks depends on shoot secondary growth.
Keywords: acorns; Mediterranean climate; nitrogen; non-structural carbohydrates; Quercus faginea; quercus ilex subsp. ballota; Stem diameter; Xylem

An increase in canopy cover leads to masting in Quercus ilex - Camarero, J. Julio; Albuixech, Jorge; López-Lozano, Raúl; Casterad, M. Auxiliadora; Montserrat-Martí, Gabriel (Trees, 2010)
Masting is the intermittent and synchronous production of large crops, but its relation to tree growth remains elusive despite the ecological relevance of mast seeding. The production of huge fruit crops has been linked to the accumulation and consumption of resources as nutrients and carbohydrates, but no conclusive assessment has supported this assumption. To evaluate if masting takes place once trees’ canopies reach maximum foliage, changes in canopy cover were measured in Quercus ilex susbp. ballota stands before and after a masting event using the normalized difference vegetation index (NDVI). The results on the whole underline that masting in Q. ilex occurred once maximum levels of NDVI and canopy cover were reached. After the masting event, NDVI dropped, leaf shedding increased and trees produced shorter shoots, narrower tree rings and fewer acorns than before the masting event. These ﬁndings support our contention that an increase in canopy cover precedes masting.
Keywords: acorn; canopy cover; Mast seeding; quercus ilex subsp. ballota; Remote sensing

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity